Procaine excites nociceptors in cultures from dorsal root ganglion of the rat - Vlachová, V; Vitásková, Z; Vyklický, L; Orkand, R K (Neuroscience letters, 1999)
Procaine, a classical local anesthetic, produces, at low concentration (2-200 microM), excitation in a distinct population of small sensory neurons isolated from newborn rats (2D) and cultured for 1-5 days. The excitation or inward current (>50 pA) induced by procaine was observed in 59 out of 78 neurons. Nearly all these procaine-sensitive neurons (56 of 59) were also sensitive to capsaicin while 8 procaine-insensitive neurons responded to capsaicin (1 microM). In procaine-sensitive neurons tested for responsiveness to noxious heat, a 10 s temperature ramp from 24 to 48 degrees C induced an inward current of 413 +/- 47 pA (SEM, n = 27) and this current was enhanced, in the presence of procaine, about 3-fold (2.8 +/- 0.4, SEM, n = 27). The responses to procaine were concentration dependent and underwent pronounced tachyphylaxis after repeated applications. The voltage-current relationship exhibited outward rectification and the apparent reversal at 25 +/- 4.2 mV (SEM, n = 9) suggesting that the current is carried by cations including Ca2+. This procaine effect may offer an explanation for toxic consequence of the clinical use of local anesthetics.
Keywords: Nociceptors; kultivované buňky; Ganglia, Spinal; Rats; Animals, Newborn; neurony aferentní; vápník; vysoká teplota; kapsaicin; nociceptory; novorozená zvířata; Procaine; prokain; krysa rodu Rattus; Calcium; Cells, Cultured; Neurons, Afferent; zvířata; tachyfylaxe; Anesthetics, Local; Tachyphylaxis; spinální ganglia; Hot Temperature; Capsaicin; anestetika lokální; Animals